Uji Efektivitas Ekstrak Lidah Mertua (Sansevieria trifasciata) untuk Menyembuhkan Luka Bakar pada Hewan Coba Kelinci (Oryctolagus cuniculus) - Ervianingsih Ervianingsih Ervianingsih; Izal Zahran; Hurria Hurria; Novita Imeldha (Jurnal Farmasi Indonesia, 2020)
The Lidah Mertua Plants (Sansevieria trifasciata) have active compounds namely Saponin, Polifenol, and Flavonoids that are able to work as antibacterials. Saponin content in the extracts of lidah mertua also work to help the formation of collagen is effective in accelerating the healing process of burns. The purpose of this study was to determine the effectiveness of healing of burns in rabbit animal experiments (Oryctolagus cuniculus) using ethanol extract of lidah mertua (Sansevieria trifasciata). The type of this study was pre experiment in which there were 5 treatments, ie 3 treatments and 2 controls with concentrations of 10% b/v, 15% b/v, and 20% b/v, and negative control using aquadest and positive control using bioplacenton. This sample was extracted by maceration method using ethanol 70%. The results showed that the extract of lidah mertua can heal burns, this was based on the results of anova test at the level of 95% confidence where F arithmetic (30)> F table (2.35) which means the hypothesis accepted. Followed by the BNT test (Beda Real Smallest) showed that the extract of tongue-in-law with concentration of 10% b/v, 15% b/v, and 20% b/v could produce different effect significantly, with optimum effect was tongue extract with 20% concentration.